The effects of internet gaming and social media use on physical activity, sleep, quality of life, and academic performance among university students in Hong Kong: A preliminary study - Carrie Kwok; Pui Yu Leung; Ka Ying Poon; Xavier C. C. Fung (Wolters Kluwer Medknow Publications, 2021)
Introduction: With the rapid increase in the prevalence of the Internet and/or smartphone usage worldwide in the last decade, engagement in internet gaming and social media may be problematic and may lead to negative consequences on mental and physical health among young adults. The main objectives of the present study are (1) to investigate how internet gaming and social media impact on physical activity, sleep quality, quality of life (QoL), and academic performance of university students in Hong Kong and (2) to investigate how physical activity and sleep associate with QoL and academic performance of university students in Hong Kong. Methods: This study employed a longitudinal design with 3-month duration. Hong Kong university students (n = 15; 4 males; mean age = 26.87 years) completed the questionnaires, wore a device to measure their physical activity and sleep, provided screen time data showing the time usage of applications on gaming and social media categories, and academic transcript for the study. Results: Internet gaming was negatively correlated with physical activity and psychological QoL (rs = −0.49 to −0.62); social media use was negatively correlated with physical activity and sleep quality (rs = −0.48 to −0.63); internet gaming and smartphone addiction were negatively correlated with academic performance (rs = −0.51 to −0.53); physical activity was positively correlated with psychological QoL (rs = 0.49). Conclusion: The results emphasized that internet gaming and smartphone addiction tend to have negative impact on physical activity, psychological QoL, sleep, and academic performance. The findings may be regarded as a direction for health-care providers to develop and evaluate the intervention to treat the specific type of internet/smartphone overuse.